PENGAKUAN PENDAPATAN PADA PT. JASA KONTRUKSI BERDASARKAN PSAK 72 - Setiawan, Aris; Fransiska, Diana; Yahya, Rizki Fakhrul (Program Studi Akuntansi Universitas Panca Bhakti, 2023)
The Research Study was conducted to analyze the revenue recognition of construction servicesbased on the Statement of Financial Accounting Standards (PSAK 72). The subject of this study isone of the construction service companies PT. Mighty Borneo. The method used in this study isqualitative research. The results of this study show that PT. Borneo Perkasa conducts revenuerecognition using the phased method of over-the-clock contracts. The company recognizes revenuebased on a percentage of the project completion rate. The amount of the completion percentagerate is measured using the physical progress method, which is based on a report from the SiteEngginering Manager (SEM) and the costs incurred to complete the project. However, thecalculations carried out by the company have not fully referred to the Statement of FinancialAccounting Standards (PSAK 72).